Elevated cyclic AMP concentration in streptomycin-dependent Escherichia coli. - Polglase, W J (1978)
Streptomycin-dependent Escherichic coli B and K-12 cultures, which have relaxed catabolite repression when grown to glucose-salts medium, have an elevated concentration of cyclic AMP.